Komposit Kitosan-Zeolit : Potensi Pemanfaatannnya sebagai Adsorben CO2 - Riva Ismawati; Setiyo Prajoko (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2018)
The world has paid special attention to the increasing of CO2 concentrations in the atmosphere. In climate change issue, CO2 gas as part of greenhouse gases plays an important role in controlling earth surface temperature. Several CO2 gas capture techniques have been reported. However, information on the utilization of potential natural materials as CO2 adsorbents is still small. This study aims to determine the potential of chitosan zeolite composites as CO2 adsorbents. Various literature is used to analyze the properties of zeolites, chitosan and the potential of chitosan- zeolite composites as CO2 adsorbents. The results show the possibility of utilizing zeolite-chitosan composites as CO2 adsorbents.